A re-analysis in exploring the association between temperature and COVID-19 transmissibility: an ecological study with 154 Chinese cities. Issue 2 (27th August 2020) - Ran, Jinjun; Zhao, Shi; Han, Lefei; Liao, Gengze; Wang, Kai; Wang, Maggie H.; He, Daihai
Exploring the role of ambient temperature in coronavirus disease 2019 (COVID-19) transmission is of importance in understanding the patterns of the epidemic. Yao et al. [1] concluded that there were no significant associations of COVID-19 transmissibility with temperature and ultraviolet (UV) radiation in 62 Chinese cities. Inspired by the nonlinear dose–response relationship between ambient temperature and influenza transmissibility explored previously [2, 3], we argue that the association between COVID-19 transmissibility and temperature might be complex in nature, which may be overlooked by a linear analytical framework. We, therefore, examined the likelihood of a nonlinear association between COVID-19 transmissibility and ambient temperature. In this national ecological study across 154 Chinese cities, the ambient temperature was found to have a nonlinear negative association with COVID-19 transmissibility https://bit.ly/3esw8rc